Oncology. Selected lectures (Experimental Oncology, 2011)
Review of the book: Oncology. Selected lectures for students and physicians. Edited by V.F. Chekhun, academician of NAS of Ukraine — Kyiv, 2010. — 768 pp. (in Ukrainian)